Lyrics to activism: Analyzing Gojira's “Amazonia” on Amazon rainforest environmental advocacy through Van Dijk’s concept - Luthfan Aulia Fathan; Tri Rina Budiwati (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2026)
This study employs Teun A. van Dijk’s framework of Critical Discourse Analysis (CDA) to examine the deeper socio-political discourse embedded within Gojira’s song Amazonia. Utilizing a qualitative descriptive methodology, the research is conducted in two phases: an initial stage of library research for data collection and theoretical grounding, followed by systematic textual analysis. The investigation relies on the song’s lyrics and supporting literature to uncover its profound meaning and broader social context. A systematic dissection of the text reveals a potent discourse of resistance against capitalist exploitation and environmental plunder. The song functions as an artistic expression of grief and mourning for the Amazon rainforest’s extensive anthropogenic destruction. The analysis is structured across three discursive layers as conceptualized by van Dijk. At the microstructure level, the study identifies prominent stylistic and rhetorical devices—notably antithesis, symbolism, and metaphor—that intensify the song’s message. The superstructure analysis examines the overall compositional scheme, demonstrating how lyrical segments are cohesively organized to build a compelling narrative arc. Finally, the macrostructure uncovers the song’s central themes: environmental destruction, systemic exploitation, and the underlying motives driving this crisis. This layer connects the text to social cognition and context, emphasizing the causal relationship between human activity and ecological damage. The research underscores the value of analyzing artistic works as vehicles for socio-environmental critique. It concludes that Amazonia serves as a deliberate tool for advocacy, raising environmental awareness and inspiring activism to confront the ongoing crisis facing the Amazon rainforest.